Obstructive sleep apnoea: a cause of chronic cough. - Birring, S; Ing, A; Chan, K; Cossa, G; Matos, S; Morgan, MD; Pavord, I (2007)
Chronic cough is a common reason for presentation to both general practice and respiratory clinics. In up to 25% of cases, the cause remains unclear after extensive investigations. We report 4 patients presenting with an isolated chronic cough who were subsequently found to have obstructive sleep apnoea. The cough improved rapidly with nocturnal continuous positive airway pressure therapy. Further studies are required to investigate the prevalence of coexistence of these common conditions.